Modeling and Simulation of Fuel cell (Dicks Larminie Model) based 3-Phase Voltage Source Inverter - Gaurav Sachdeva (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In the present work, performance of three phase voltage source inverter, while feeding different power factor loads, has been investigated. Fuel cells model namely Dicks Larminie model is used in input side as a DC source while dynamic load has been used at the output side. Dynamic load used is induction motor (IM). Performance of IM has been investigated under various loading conditions. ANN based control strategy has been proposed to find the conduction angle of a 3-Phase VSI and verified for IM load. Simulations have been performed using PSIM 7.0.5 and MATLAB 7.0.4.DOI:http://dx.doi.org/10.11591/ijece.v4i5.5508